Re-designing materials for biomedical applications: from biomimicry to nature-inspired chemical engineering. (11th February 2019) - Perera, Ayomi S.; Coppens, Marc-Olivier
Abstract : Gathering inspiration from nature for the design of new materials, products and processes is a topic gaining rapid interest among scientists and engineers. In this review, we introduce the concept of nature-inspired chemical engineering (NICE). We critically examine how this approach offers advantages over straightforward biomimicry and distinguishes itself from bio-integrated design, as a systematic methodology to present innovative solutions to challenging problems. The scope of application of the nature-inspired approach is demonstrated via examples from the field of biomedicine, where much of the inspiration is still more narrowly focused on imitation or bio-integration. We conclude with an outlook on prospective future applications, offered by the more systematic and mechanistically based NICE approach, complemented by rapid progress in manufacturing, computation and robotics. This article is part of the theme issue 'Bioinspired materials and surfaces for green science and technology'.